Development of Meaning and Purpose Audio Script for Micro Learning Course - Sungkono Sungkono; Firdiawan Ekaputra (PT ARRUS Intelektual Indonesia, 2024)
The purpose of this study was to determine the quality of the audio script of meaning and purpose in micro learning courses developed. This development research uses the 4 D model, which consists of definition, design, development, and dissemination stages. In the developed micro-learning course, the quality of the audio script of meaning and purpose was assessed through open and closed questionnaires using a Likert scale. The audio script of the meaning and purpose of the micro-learning course that has been developed is then assessed by media and material experts, and field tested on a limited and small scale. The limited scale trial sample consisted of 10 students on a limited scale and 25 students on a small scale. Consisting of both quantitative and qualitative data, this study includes feedback and recommendations from media experts, material experts, and field trials. The results of the field trial have shown that the designed audio script of the meaning and purpose of micro-learning courses can be used well. Based on the assessment from the limited and small-scale field tests, the quantitative data was converted into the quality level of the audio script of the meaning and purpose of microlearning courses. The results of the limited scale field test showed an average of 87.14%, and the limited scale field test showed an average of 91.86%.